The Evolution of the Approaches to the Problem of Hereditary Title - M. S. Abramenkov (Московский журнал международного права)
The contemporary state of affairs is often characterized by the fact that hereditary relationships transcend the borders of one state. These cases are not unique due to migration of people, mixed marriages, etc. This leads to a problem of regulation of social relationships in the process of internationalization. Thus hereditary relationships having international character should be governed by the norms of a certain national legal order or of several such legal orders. The main task of the court or any other body in this case is to determine which national order is to be complied with, that is which legal order will serve as lege causae in a particular case Initially lege causae was understood as a written source of law, being in force on a particular territory, which included norms both from public and private, including hereditary, law. Later on the term lege causae was used in respect of the title of the state, which as included in conflict rules is relevant for the purposes of regulation of private legal relationships, related to the legal orders of several states, including the hereditary relationships.